Living Standards of Tunisian Households in the Midst of the COVID-19 Pandemic - Alfani, Federica (World Bank, Washington, DC, 2021)
The COVID-19 pandemic has had unprecedented negative socioeconomic effects on the lives of millions of people across the world, particularly among the most vulnerable groups. The COVID-19 outbreak has exacerbated the issues countries were facing before the pandemic such as the unequal access to basic services, markets, labor, and capital. Using five rounds of high-frequency telephone surveys collected by the Tunisian National Institute of Statistics in collaboration with the World Bank, this paper analyzes the deterioration in households’ welfare due to COVID-19, focusing on changes in the labor market. The results show that although employment has now rebounded to pre-crisis levels among the respondents, labor income among wage workers and particularly the self-employed is still below pre-pandemic levels. More than half of the households interviewed report a worsening of their living standards relative to before the start of the pandemic, and for about 40 percent of the poorest, welfare levels have continued to deteriorate. In addition, price increases and a reduction in remittances threaten to undo the progress that has been achieved in raising living standards. While waiting for the economy to rebound, the most vulnerable households will continue to need income support.